2007
DOI: 10.1111/j.1813-6982.2007.00114.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Cyclicality of South African Fiscal Policy

Abstract: This paper examines the cyclicality of government revenue, spending and the key fiscal balances in South Africa during 1972-2001. The results suggest that while government revenues were largely acyclical, government spending appears to have been predominantly counter-cyclical, in line with the recommendations of neoclassical analysis. In addition, countercyclical government spending appears to have translated into a countercyclical policy stance overall. This finding contrasts markedly with the results from ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…This finding is contrary to the dominant literature showing that fiscal policy tends to be pro-cyclical in developing countries (Carmignani, 2010; Kassouri and Altıntaş, 2021). However, the findings of this study are consistent with Thornton (2007) who showed that South African fiscal policy is counter-cyclical.…”
Section: Resultssupporting
confidence: 92%
“…This finding is contrary to the dominant literature showing that fiscal policy tends to be pro-cyclical in developing countries (Carmignani, 2010; Kassouri and Altıntaş, 2021). However, the findings of this study are consistent with Thornton (2007) who showed that South African fiscal policy is counter-cyclical.…”
Section: Resultssupporting
confidence: 92%
“…The same method yielded no statistically significant correlation between government revenue and GDP growth. Thornton's (2007:262‐263) evidence of counter‐cyclical government expenditure confirms the results of Du Plessis (2006), but his evidence on the acyclicality of government revenue stands in sharp contrast with Du Plessis and Boshoff's (2007) evidence on the highly cyclical pattern of government revenue in South Africa.…”
mentioning
confidence: 78%
“…The recent South African literature on the topic has seen the use of four different empirical measures, viz. : (i) using a structural budget balance (Swanepoel and Schoeman, 2003), (ii) the calculation of cyclically adjusted fiscal impulse (Horton, 2005; Ajam and Aron, 2007; Swanepoel, 2007), (iii) the univariate analysis of government revenue and expenditure (Du Plessis, 2006; Thornton, 2007), and (iv) using a structural vector‐autoregression (SVAR) to identify the fiscal policy (Frankel et al. , 2007).…”
Section: Literaturementioning
confidence: 99%
See 2 more Smart Citations